2013
DOI: 10.1111/1742-6723.12128
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in emergency department length of stay using an early senior medical assessment and streaming model of care: A cohort study

Abstract: Objective : Australian EDs are required to conform to the National Emergency Access Target (NEAT): patients must be discharged within 4 h of arrival. The aim of the present study was to determine if a model of care called Senior Assessment and Streaming (SAS) would increase the proportion of patients achieving NEAT. Methods:Stable, ambulant patients considered to have problems that early consultant-level assessment was likely to improve processing efficiency were streamed through a dedicated clinical area st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…In the final group of 15 studies, the intervention was a senior doctor-led team triage where the senior doctor was accompanied by a team of other health professionals such as nurses and technicians. In five of these studies, the team included junior doctors in addition to nurses or technicians 24 31 32 36 37. See table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the final group of 15 studies, the intervention was a senior doctor-led team triage where the senior doctor was accompanied by a team of other health professionals such as nurses and technicians. In five of these studies, the team included junior doctors in addition to nurses or technicians 24 31 32 36 37. See table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Using the EPHPP global rating decision tool, 4 studies were assessed as being of strong quality,23 34 35 37 9 of moderate quality18 20 25 26 27 29 31 32 39 and 12 of weak quality. None of the studies were double blinded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different methods have been proposed based on the fast track concept, such as using functional principles to separate patients into streams on the basis of complexity rather than acuity [12]; separating high-and low-variability patients to improve throughput and reduce LOS in ED [30]; and improving ED LOS using an early senior medical assessment and streaming model of care [31].…”
Section: Fast Track Treatment (Ftt)mentioning
confidence: 99%
“…The experiences described by care programs have demonstrated that, through appropriate geriatric assessments, identification of risks, and support strategies in the transition of the care, it is possible to reduce the return of the elderly to the ES, avoid admissions, obtain greater satisfaction, and reduce hospital costs (5,16,(18)(19) . Therefore, these studies offer different examples that can encourage new practices in the ES together with the reality of each institution.…”
Section: 6mentioning
confidence: 99%